Investigating Students Knowledge and Social Awareness of the Community of Religious Social Activist Minangkabau: A Community Based Reseach In West Sumatra, Indonesia - Haviz, M.; Afwadi, Afwadi; Selamat, Kasmuri; Maris, Ika Metiza; Hanif, Akhyar; Trisoni, Ridwal; Effendi, Yusrizal (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2019)
AbstractThe study aims to investigate the knowledge of junior high school students on Islamic religious education materials and the social awareness of the Minangkabau religious social activist community. The subject matter of Islamic education is al-Quran, al-Hadith, al-Tarikh, al-Fiqh, al-Akhlaq, al-Aqidah and Arabic language. The research method is community based research. The general steps of the CBR are cycles in four stages, namely, laying the foundation, planning, gathering/analyzing information and action to finding. This study involves junior high school students and the community of Minangkabau religious social activist. This study found that these students have poor Islamic religious knowledge in seven materials. The Minangkabau religious social activists have a high social awareness when activities strengthen formal education with Islamic non-formal education is carried out. The study also provides recommendations on the need for further on finding action for the development of madrasah diniyah takmilyah wustha (MDTW) by exploring Minangkabau values. The findings of this study have implied that this research is an effort that can be done to stop the “silent or slow running phase” of the Minangkabau (surau) mosque and madrasa. This study has also reaffirms that Minangkabau surau and madrasah are not lost or will be lost in Minangkabau, West Sumatra Indonesia.AbstrakPenelitian ini bertujuan untuk menyelidiki pengetahuan siswa SMP pada materi pendidikan agama Islam dan kesadaran sosial dari komunitas aktivis sosial religius minangkabau. Subyek pendidikan Islam adalah materi al-Quran, al-Hadits, al-Tarikh, al-Fiqh, al-Akhlaq, al-Aqidah dan bahasa Arab. Metode penelitian adalah penelitian berbasis komunitas (community based research). Langkah-langkah umum CBR adalah siklus dalam empat tahap: meletakkan fondasi, perencanaan, pengumpulan / analisis informasi dan tindakan untuk menemukan. Penelitian ini melibatkan siswa SMP dan komunitas aktivis sosial keagamaan minangkabau. Studi ini menemukan bahwa para siswa ini memiliki pengetahuan agama Islam yang buruk dalam tujuh materi. Para aktivis sosial keagamaan minangkabau memiliki kesadaran sosial yang tinggi ketika kegiatan memperkuat pendidikan formal dengan pendidikan non-formal Islam dilakukan. Studi ini juga memberikan rekomendasi tentang perlunya untuk lebih lanjut menemukan tindakan untuk pengembangan madrasah diniyah takmilyah wustha (MDTW) dengan mengeksplorasi nilai-nilai minangkabau. Temuan penelitian ini telah mengimplikasikan bahwa penelitian ini merupakan upaya yang dapat dilakukan untuk menghentikan